الأساليب التربوية الخاطئة في تنشئة الطفل في المنظور الإسلامي - حسن هدله, سناء (University of Eloued جامعة الوادي, 2011)
يتضمن هذا البحث نظرة سريعة حول مسؤولية التربية، وهدفها في حياة الطفل ثم عرض للأساليب الخاطئة التي تسلكها بعض الأسر في تنشئة أولادها، ومقارنتها بالنهج التربوي الإسلامي القويم، يتبعه ذكر لمزايا الأسلوب التربوي الإسلامي. Abstracts This research includes a quick look on the responsibility of education and its goal of a child's life and then view the methods wrong routes some families in the upbringing of their children, compared with the True Islamic educational approach, followed by mention of the advantages of the Islamic educational method.
مقال بمجلة البحوث والدراسات
Keywords: أساليب تربوية - تنشئة الطفل - منظور إسلامي